2020
DOI: 10.1101/2020.06.05.136481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection leads to acute infection with dynamic cellular and inflammatory flux in the lung that varies across nonhuman primate species

Abstract: SummaryThere are no known cures or vaccines for COVID-19, the defining pandemic of this era. Animal models are essential to fast track new interventions and nonhuman primate (NHP) models of other infectious diseases have proven extremely valuable. Here we compare SARS-CoV-2 infection in three species of experimentally infected NHPs (rhesus macaques, baboons, and marmosets). During the first 3 days, macaques developed clinical signatures of viral infection and systemic inflammation, coupled with early evidence … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
2
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 29 publications
2
45
2
10
Order By: Relevance
“…Differently than was observed in humans and previous reported data in RM, we did not detect an increase in the number of neutrophils as these responses may have come up earlier than week after infection as shown by others 18 . Common to both species was the observation that animals with higher levels of myeloid and lymphoid cell infiltration in the lung had worse disease outcomes.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Differently than was observed in humans and previous reported data in RM, we did not detect an increase in the number of neutrophils as these responses may have come up earlier than week after infection as shown by others 18 . Common to both species was the observation that animals with higher levels of myeloid and lymphoid cell infiltration in the lung had worse disease outcomes.…”
Section: Discussioncontrasting
confidence: 97%
“…Following exposure, AGM and RM have high levels of virus replication in the respiratory tract for up to two weeks, and both species develop pulmonary pathology characteristic of COVID-19, that varies from very mild to severe 17 . Other groups have described the very early immune events in SARS-CoV-2 infected rhesus macaques, with perturbation of monocytes populations, increased macrophages in lungs, and cellular activation in blood all happening a few days following the infection 18 .…”
mentioning
confidence: 99%
“…While several recent studies have reported on T cell dynamics in peripheral blood of patients (17)(18)(19)(20)(21), early immune responses, particularly in lymphoid and respiratory tissues, are challenging to study in humans. Rhesus macaques have emerged as a robust model for SARS-CoV-2 (22)(23)(24)(25)(26)(27). Because healthy rhesus macaques infected with SARS-CoV-2 resist immediate re-challenge with the virus (24,27), we hypothesized that understanding the CD4 Tfh and germinal center (GC) response following exposure to SARS-CoV-2 will provide a framework for understanding immune mechanisms of protection thereby providing evidence-based data on which to select an effective vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] Subsequently, testing for in vivo safety and efficacy in an established large animal model of SARS-Cov-2 infection such as rhesus macaque or baboon will be conducted to further support an investigational new drug application. [27] While other nanobodies have been produced in large scale current Good Manufacturing Practice facilities by fermentation, there is no guarantee that NIH-CoVnb-112 constructs can be produced in sufficient quantities at reasonable cost. Exploration of the manufacturing parameters will be critical for product development.…”
Section: Discussionmentioning
confidence: 99%